Conceptualisation of knowledge construction in community service-learning programmes in nursing education - Sindi Z. Mthembu; Fikile G. Mtshali (AOSIS, 2013)
Background: Practices in higher education have been criticised for not developing and preparing students for the expertise required in real environments. Literature reports that educational programmes tend to favour knowledge conformation rather than knowledge construction; however, community service learning (CSL) is a powerful pedagogical strategy that encourages students to make meaningful connections between the content in the classroom and real-life experiences as manifested by the communities. Through CSL, learning is achieved by the active construction of knowledge supported by multiple perspectives within meaningful real contexts, and the social interactions amongst students are seen to play a critical role in the processes of learning and cognition. This article reflects facilitators' perspective of the knowledge construction process as used with students doing community service learning in basic nursing programmes. Objectives: The aim of this article was to conceptualise the phenomenon of knowledge construction and thereby provide educators with a shared meaning and common understanding, and to analyse the interaction strategies utilised by nurse educators in the process of knowledge construction in community service-learning programmes in basic nursing education. Method: A qualitative research approach based on a grounded theory research design was used in this article. Two nursing education institutions were purposively selected. Structured interviews were conducted with 16 participants. Results: The results revealed that the knowledge construction in community service-learning programmes is conceptualised as having specific determinants, including the use of authentic health-related problems, academic coaching through scaffolding, academic discourse-dialogue, interactive learning in communities of learners, active learning, continuous reflection as well as collaborative and inquiry-based learning. Upon completion of an experience, students create and test generated knowledge in different contextual health settings. Conclusion: It was concluded that knowledge is constructed by students as a result of their interaction with the communities in their socio-cultural context and is mediated by their prior concrete experiences. The implication of this is that students construct knowledge that can be applied in their future work places.